ARTIFICIAL INTELLIGENCE - SOCIETY AND THE FUTURE - Shukurov Sh. Z. (Galaxy International Interdisciplinary Research Journal, 2023)
This article was prepared on the topic of artificial intelligence, which has become the most relevant and in demand today. In the introduction of the article, the author briefly reveals its history, concept and significance in society. In the main part, he explains the positive and negative aspects of artificial intelligence, and also, based on analysis, evaluates its role and influence in the future. At the end of the article, he sums up the results and makes a number of recommendations for solving the scientific problem.